PEMEROLEHAN DEIKSIS BAHASA INDONESIA BAGI ANAK USIA 2,5 TAHUN - Asri, Wahyu Kurniati (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2010)
This research aims to know how the acquisition of Indonesian deixis for 2.5 years child (a case study on the results of mixed marriages). The deixis that would be uncovered are (1) temporal deixis, (2) locative deixis, (3), persona deixis, and (4) demonstrative deixis. The result of study shows that in general, it can be concluded that Diana has not been able to master deixis overall. Some deixis have been understood but she cannot exactly mention them correctly, for example, temporal, personal, and demonstrative locative deixis. Diana has master deixis demonstrative 'that' in understanding and producing it compared with others. Diana was able to answer questions asked by his father in German, although she cannot speak German, as he speaks Indonesian.